Adsorptive removal of Cr(VI) from wastewater using termite mound blended with chicken eggshell as an adsorbent: Equilibrium and kinetic approaches - Mebratu Ergete Mengistu; Yasin Ahmed Waday; Wondwosen Sime Geleta; Yigezu Mekonnen Bayisa; Dereje Tadesse Mekonnen (Desalination and Water Treatment)
In the present study, environmental friendly adsorbent was produced from termite mound blended with chicken eggshell through calcination process to remove Cr(VI) from contaminated water. In line with this, the synthesized termite mounds blended with chicken eggshells (TMESP) adsorbent was assessed depending on their structural patterns, functional group, optical properties, and loss of mass using XRD, FTIR, UV–Vis spectra, and TGA, respectively. The effects of adsorption parameters, pH, adsorbent dosage, initial Cr(VI) concentration, and contact time on Cr(VI) removal efficiency were examined by design expert via central composite design. Thus, the maximum Cr(VI) removal efficiency of 99.79 % achieved at pH of 7, adsorbent dosage of 6 g/L, initial Cr(VI) concentration of 40 mg/L, and contact time of 75 min. The adsorption behavior of TMESP adsorbent evaluated using Langmuir (R² = 0.99428), Freundlich (R² = 0.99725), and Temkin (R² = 0.866) isotherm models to examine the distribution of Cr(VI) ions across active sites on adsorbent surface. The kinetic analysis revealed pseudo-second-order model (R² = 0.9998) best described the adsorption process, outperforming the pseudo-first-order (R² = 0.98982) and intra-particle diffusion models (R² = 0.5691). These results suggest chemisorption is the dominant mechanism and indicate synthesized adsorbent can implement to adsorb Cr(IV) ions.